A Study Into The Effects Of eLearning On Higher Education - Singh, G.; O'Donoghue, J.; Worton, H. (Journal of University Teaching and Learning Practice, 2005)
The Internet is a technological development that has thepotential to change not only the way society retains andaccesses knowledge but also to transform andrestructure traditional models of higher education,particularly the delivery and interaction in and with coursematerials and associated resources. Utilising the Internetto deliver eLearning initiatives has created expectationsboth in the business market and in higher educationinstitutions. Indeed, eLearning has enabled universities toexpand on their current geographical reach, to capitaliseon new prospective students and to establish themselvesas global educational providers. This paper examines theissues surrounding the implementation of eLearning intohigher education, including the structure and delivery ofhigher education, the implications to both students andlecturers and the global impact on society.